Serum levels of GDF15 are reduced in preeclampsia and the reduction is more profound in late-onset than early-onset cases. (July 2016) - Chen, Qi; Wang, Yao; Zhao, Min; Hyett, Jonathan; da Silva Costa, Fabricio; Nie, Guiying
Highlights: Serum levels of GDF15 significantly increased across gestation in normal pregnancy. Serum levels of GDF15 were significantly reduced in women with preeclampsia. Serum levels of GDF15 were not altered in the first trimester in women who later developed late-onset preeclampsia. Abstract: Background: Preeclampsia is a pregnancy specific disorder affecting 3–5% of pregnancies worldwide. It is clinically divided into early-onset and late-onset subtypes. Placental factors are involved in the pathogenesis of preeclampsia. Growth differentiation factor 15 (GDF15), a protein of the transforming growth factor beta superfamily, is highly expressed in the placenta. However, it is unclear whether the circulating levels of GDF15 are altered in preeclampsia at the time of or prior to disease presentation. Methods: Serum samples across three trimesters from 29 healthy pregnancies, third trimester sera from 34 women presenting with preeclampsia (early-onset n = 16, late-onset n = 18) and 66 gestation-age-matched controls, and sera at 11–13 weeks of pregnancy from women who later did (n = 36) or did not (n = 33) develop late-onset preeclampsia, were examined for GDF15 by ELISA. Results: Serum GDF15 levels increased significantly with gestation in normal pregnancy. Serum GDF15 was significantly reduced in the third trimester in women presenting with preeclampsia compared to their gestation-age-matched controls. This reduction was apparent in both early-onset and late-onset subtypes, but it was more profound in late-onset cases. At 11–13 weeks of gestation, however, serum levels of GDF15 were similar between women who subsequently did and did not develop late-onset preeclampsia. Conclusion: Serum GDF15 increased with gestation age, reaching the highest level in the third trimester. Serum GDF15 was significantly reduced in the third trimester in women presenting with preeclampsia, especially in late-onset cases. However, serum GDF15 was not altered in the first trimester in women destined to develop late-onset preeclampsia.